Geopolitical Situation in The Central Asian Region at The Present Stage - Ibragimova Mohinur Sanat qizi (Genius Journals, 2022)
The Taliban victory has seriously boosted the morale of extremism around the world. The taliban's success has markedly emboldened various groups such as ISis or alQaeda. These organizations are excited and capable of more attacks in the foreseeable future. Islamic extremists pose a huge security problem.
Keywords: thalibs; Islamic state; al-Qaeda; Central Asian region